Pedagogies in struggle: postcolonial openings from experiences of Popular Education in Bogotá, Colombia - Nabila Tavolieri (University of Bologna, 2023)
This essay first attempts to provide a brief description of what the Italian postcolonial condition is, by taking into consideration some critical points that should be addressed when thinking about decolonial pedagogy in multicultural contexts, such as colorblindness and the neoliberal management of interculturality. Then it follows some assumptions collected during 4 months of ethnographic collaborative-action research within popular and communitarian movements that provide Popular Education in some marginal areas of the city of Bogotá, Colombia. Finally, drawing on the same experiences I have been involved in, I will propose suggestions for imagining how the Italian understanding of intercultural education can be freed from coloniality. Eventually, the paper proposes the need to carry out a communitarian turn in pedagogy based on three orienting practices: memory as a dialogical and living praxis, territory as a hermeneutic tool and methodology, and politics of love and care. Given this, the paper also seeks to address interculturality as a dialogical methodology through which supporting the argument. Indeed, the postcolonial framework is considered in its resonances with Cultural Studies, Popular Studies, Popular and Critical Education, Black Studies, and The Latin American Decolonial Movement.